Evaluation method of operational effectiveness of sporting goods enterprises from the perspective of health informatics - Genghua Lei; Long Zhang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The existing evaluation methods for the operational effectiveness of sporting goods enterprises do not consider the information synergy among the indexes when determining the index weight, which has a certain impact on the fitting degree of the evaluation results. This paper proposes an evaluation method for the operational effectiveness of sporting goods enterprises from the perspective of health informatics. From the four aspects of repayment ability, operation ability, profitability, and growth ability of sporting goods enterprises, this paper selects indicators to establish a rating index system. The algorithm of evaluation index information association strength is designed, and the dynamic association subgroup density and collaborative structure entropy of the index system are calculated to obtain the Information Collaborative association strength of different indexes. According to the information entropy of collaborative structure, the index weight is determined, and the evaluation model of operation effectiveness is established. The experimental results show that the proposed evaluation method is superior to the existing evaluation methods in three parameters: GFI, PGFI and NFI, which shows that the design method has a good degree of fit and can provide reference for the business evaluation of sporting goods enterprises.